ANALISIS TINGKAT KEPUASAN KONSUMEN RESTORAN WAROENG HOTPLATE ODON CIBANTENG, BOGOR, JAWA BARAT - Tasya Amanda; Rita Nurmalina (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2018)
The competition among restaurants increases due to citizen’s new lifestyle for visiting restaurant. The purpose of this study is to analyze the consumer decision of making process, the customer satisfaction, and to formulate the recommendation for attributes improvement. Data are collected from 143 respondents using convenience sampling method and processed by Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The analytical results showed that the customer was generally 72,8 percent satisfied and the restaurant should give a high attention on the price, the availability of parking area, and supporting facilities to be improved because the importance scores of them were high but the pee scores were still low. To increase the customer satisfaction, restaurant should improve its performance by expanding the parking area, improving the supporting facilities, optimalizing food portion with the price and also improve the attributes that have lower weighted-score by setting an attractive promotion, re-arranging the aesthetic space, creating advertisement, and providing autodebit service.